2016
DOI: 10.1016/j.jval.2016.08.739
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Prescribing Indicators in Public and Private Primary Health Care Facilities in Indonesia

Abstract: database contains 4,153,588 pharmacy-dispensed claims with 112,523 ingredient entries and 16,944,271 physician-dispensed claims with 2,222,342 ingredient entries. The average amount paid per CD ingredient per year for pharmacy-dispensed CDs increased by 37% from 2011 to 2012 and 67% from 2012 to 2013, while physiciandispensed increased by 14% from 2011 to 2012 and 20% from 2012 to 2013. The current CA AB 378 regulation does not significantly reduce CD cost, in fact the cost increased. The change in cost of CD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
0
5
2
Order By: Relevance
“…The most antibiotic used at the hospital setting in this study was cefadroxil, which was indicated for post-operative treatment. The percentages of encounters in which an antibiotic found in study by Yuniar 23 were 42.8% and 39.4%, higher than finding of our study in hospital setting. Finding of study by Dinge 24 for the percentages of encounters in which an antibiotic at hospital setting was 33.43%, slighly lower than our findings but still upon WHO standard.…”
Section: Percentage Of Encounters With Antibioticscontrasting
confidence: 78%
See 4 more Smart Citations
“…The most antibiotic used at the hospital setting in this study was cefadroxil, which was indicated for post-operative treatment. The percentages of encounters in which an antibiotic found in study by Yuniar 23 were 42.8% and 39.4%, higher than finding of our study in hospital setting. Finding of study by Dinge 24 for the percentages of encounters in which an antibiotic at hospital setting was 33.43%, slighly lower than our findings but still upon WHO standard.…”
Section: Percentage Of Encounters With Antibioticscontrasting
confidence: 78%
“…The averages number of drugs per encounter in this study both at primary health care center and at hospital setting were above the WHO standard. This findings were inline but still lower than previous study conducted in Indonesia by Yuniar which found that the average numbers of drugs per encounter in public and private facilities was 3.31 and 3.06, respectively 23 . Other study conducted in Indonesia by Dinge 24 found the average numbers of drugs per encounter was 2.3, better than our findings but still above the WHO standard.…”
Section: Average Number Of Drugs Per Encounterscontrasting
confidence: 70%
See 3 more Smart Citations